Practical Implementation of An-Nahdliyah Method for Improving the Ability to Read the Qur'an in TPQ Roudlotuts Taallum - Subandono, Agus; Saka, Dijan Novia; Alim, Bagus Muhamadin; Wulandari, Desi; Rosidah, Fatkhur (LP2M UIN KH.Achmad Siddiq Jember, 2023)
This research aims to assess the effectiveness of implementing the An-Nahdliyah method in enhancing Quran reading proficiency at TPQ Roudlotut Taallum. The study employs a qualitative field research approach to delve into the practical application of the An-Nahdliyah method, following the prescribed guidelines for managing Quran education centers. Various challenges are identified, including students' difficulties in comprehending learning materials, irregular attendance, and a lack of enthusiasm throughout the learning process. The findings of this study provide valuable insights into the efficacy of the An-Nahdliyah method and shed light on potential obstacles that may arise during its implementation. Penelitian ini bertujuan untuk menilai efektivitas penerapan metode An-Nahdliyah dalam meningkatkan kemampuan membaca Al-Qur'an di TPQ Roudlotut Taallum. Penelitian ini menggunakan pendekatan penelitian lapangan kualitatif untuk menyelidiki implementasi praktis metode An-Nahdliyah, dengan mengikuti pedoman yang ditetapkan untuk pengelolaan pusat pendidikan Al-Qur'an. Beberapa tantangan yang diidentifikasi meliputi kesulitan yang dihadapi siswa dalam memahami materi pembelajaran, kehadiran yang tidak teratur, dan kurangnya antusiasme selama proses pembelajaran. Temuan penelitian ini memberikan wawasan tentang efektivitas metode An-Nahdliyah dan mengungkapkan hambatan potensial yang mungkin timbul selama implementasinya.